Resilient and Self‐reliant Life: South Sudanese Refugees Imagining Futures in the Adjumani Refugee Setting, Uganda. (1st November 2018) - Schiltz, Julie; Derluyn, Ilse; Vanderplasschen, Wouter; Vindevogel, Sofie
Abstract : Resilience and self‐reliance have become central in humanitarian responses to refugee situations. Based on a two‐year longitudinal qualitative study, this article explores how South Sudanese refugee youngsters in Uganda imagine and act towards their futures, and questions what resilience and self‐reliance can mean in the temporary space of the refugee camp. Youngsters need to become accustomed to a future without substantial progress, or be ready to play the game of chance. As such, a resilience and self‐reliance policy not only reveals the powerlessness of refugee youth, but also the limits of a humanitarian project to seek actual solutions to refugee situations.